Peranan Notaris Sebagai Pejabat Pembuat Akta Dikaitkan Dengan Pasal 55 KUHP - Tigris, Howard Julio; Yusuf, Chandra; Santosa, Irwan (LPPM Institut Pendidikan Nusantara Global, 2024)
Article 16 Paragraph (1) Letter a Law Number 2 of 2014 Concerning the Office of a Notary Public which emphasizes the obligation of a notary to act in a trustful, honest, thorough, independent, impartial manner and protect the interests of the parties involved in legal actions. However, in practice there are still notaries who commit criminal acts involving the forgery of authentic deeds. For this reason, the purpose of this study is to analyze the legal consequences and responsibilities of a notary in his position as a deed making official in making an authentic deed which indicates the participation of the criminal act of forgery. The method used in this research is normative juridical research with statutory, conceptual, analytical and case approaches which are processed using qualitative descriptive techniques. The results of the study show that the legal consequences for a notary in his position as a deed-making official in making authentic deeds indicated that there was an indication of participation in the criminal act of forgery, namely according to the UUJN it can be applied regarding dismissal/notary being dismissed from his position, according to Article 1365 of the Civil Code he is obliged to pay compensation to the aggrieved parties and according to Articles 264 and 266 of the Criminal Code in the form of imprisonment. The legal responsibility of a notary in his position as an official making a deed for indications of participating in the crime of forgery in making an authentic deed, that is, he can be criminally responsible if he fulfills the elements of error, namely being able to take responsibility, there is an inner relationship in the form of intentionality and there is no reason to erase the mistake. So that a Notary who consciously deliberately or is involved in falsifying the making of a deed can be held accountable in criminal law in the form of imprisonment and criminal administrative sanctions